Origin of plagiogranites in oceanic complexes: A case study of the Nicoya and Santa Elena terranes, Costa Rica - Whattam, Scott A. (2016)
The origin of minor leucocratic intrusions known as “plagiogranites” in oceanic complexes dominated by basaltic compositions have been debated in the literature. Here we use well preserved plagiogranites within the contrasting Santa Elena Ophiolite and the Nicoya Complex, NW Costa Rica, to investigate the origin and age of these leucocratic intrusions. Magmatic zircons of plagiogranites of the Santa Elena ophiolite and the Nicoya Complex, yield weighted mean SHRIMP 206Pb/238U ages of 125.3 ± 2.0 Ma and 90.9 ± 2.0 Ma to 88.5 ± 2.0 Ma (n = 5), respectively. These ages record the main magmatic phases of formation of these intrusions preserved in each complex. Relatively flat, unfractionated chondrite-normalized REE patterns of plagiogranites from both complexes mimic signatures of related mafic rocks, which is consistent with formation via fractional crystallization from a mafic source as opposed to partial melting of a mafic (basalt, amphibolite) protolith. In the case of the Nicoya Complex, modelling suggests that the Nicoya plagiogranites are consistent as ~ 10–15% residual liquids after fractional crystallization from its mafic parental source. Trace element systematics of the plagiogranites are consistent with an oceanic arc origin for Santa Elena and a mostly mid-ocean ridge to oceanic-plateau origin for Nicoya.